Altered intestinal permeability in patients with relapsing–remitting multiple sclerosis: A pilot study. (March 2017) - Buscarinu, Maria Chiara; Cerasoli, Benedetta; Annibali, Viviana; Policano, Claudia; Lionetto, Luana; Capi, Matilde; Mechelli, Rosella; Romano, Silvia; Fornasiero, Arianna; Mattei, Gianluca; Piras, Eleonora; Angelini, Daniela Francesca; et al.
Background: Alterations of intestinal permeability (IP) may contribute to the pathophysiology of immune-mediated diseases. Objective: We investigated the possible association between IP changes and multiple sclerosis (MS). Methods: We studied 22 patients with relapsing–remitting multiple sclerosis (RRMS) and 18 age- and sex-matched healthy donors (HDs), including five twin pairs (one concordant, and four discordant for disease). Measurement of lactulose (L) and mannitol (M; two non-metabolized sugars) levels in urine samples, after an oral load, allowed to quantify gut dysfunction. Results: The proportion of participants with increased IP was significantly higher in patients than in HDs (16/22 (73%) versus 5/18 (28%); p = 0.001). Accordingly, the L/M urinary ratio showed significantly higher values in patients than in controls ( p = 0.0284). Urinary mannitol concentration was significantly lower in patients than in controls ( p = 0.022), suggesting a deficit of absorption from intestinal lumen. Such changes did not appear related to patients' clinical–radiological features. Conclusion: The relatively high proportion of IP changes in RR-MS patients seems to confirm our work hypothesis and warrants more work to confirm the result on a larger sample, and to understand the implications for related immunological disturbances and intestinal microbiota alterations. Our finding may also have relevance for oral treatments, recently introduced in clinical practice.